The small GTPase ARF6 regulates GABAergic synapse development - Kim, Hyeonho; Jung, Hyeji; Jung, Hyunsu; Kwon, Seok-Kyu; Ko, Jaewon; Um, Ji Won (BMC, 2020)
ADP ribosylation factors (ARFs) are a family of small GTPases composed of six members (ARF1-6) that control various cellular functions, including membrane trafficking and actin cytoskeletal rearrangement, in eukaryotic cells. Among them, ARF1 and ARF6 are the most studied in neurons, particularly at glutamatergic synapses, but their roles at GABAergic synapses have not been investigated. Here, we show that a subset of ARF6 protein is localized at GABAergic synapses in cultured hippocampal neurons. In addition, we found that knockdown (KD) of ARF6, but not ARF1, triggered a reduction in the number of GABAergic synaptic puncta in mature cultured neurons in an ARF activity-dependent manner. ARF6 KD also reduced GABAergic synaptic density in the mouse hippocampal dentate gyrus (DG) region. Furthermore, ARF6 KD in the DG increased seizure susceptibility in an induced epilepsy model. Viewed together, our results suggest that modulating ARF6 and its regulators could be a therapeutic strategy against brain pathologies involving hippocampal network dysfunction, such as epilepsy.
Keywords: NUCLEOTIDE EXCHANGE FACTOR; POSTSYNAPTIC DENSITY; PRESYNAPTIC ROLE; G-PROTEINS; FAMILY; MATURATION; MSEC7-1; EFA6A; BRAG1; GIT1